Model pengembangan pendidikan karakter religius berbasis tarbiyah: Studi kasus mahasiswa program studi pendidikan agama Islam - Sari, Intan; Djunaidi, Mahbub; Maghfiroh, Lailatul (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2025)
This study develops a model of religious character education for students of Islamic Religious Education Universitas Islam Darul Ulum Lamongan. Using a grounded theory approach, this model was constructed through qualitative data analysis from 50 students in semesters 4 and 6. Data was collected through an open survey and analyzed by open coding, axial coding, and selective coding. The results identified eight key elements in the Tarbiyah model: Example, Worship Activities, Self-Reflection, Social Development, Value Integration, Belief & Love of Kindness, Real Action, and Habituation. The example of lecturers, campus religious activities, and self-reflection are the main supporting factors in the formation of religious character. The influence of social media and promiscuity is a major challenge. The TARBIYAH model is relevant to foster the religious character of Generation Z students who are multitasking but prone to disorientation of values.